1995
DOI: 10.1109/20.489779
|View full text |Cite
|
Sign up to set email alerts
|

Ferrimagnetic zinc ferrite fine powders

Abstract: Partially hverked h e powders of zinc ferrite (ZnFe;?O$ were produced by chemical aerogel synthesis. These powders showed magnetic ordering at temperatures to 250K. Upon ball milling, a much higher inversion parameter was attain4 yielhg ferrimagnetic powders having small remanence and coercive fields at room temperature. Due to the small mean particle size, superparamagnetic behavior was seen at temperatures above 25K. Powder properties were characterized by x-ray a a c t i o n , electron microscopy, calorimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…For the ZFC curve with 10 Oe magnetic field applied, spin-glass behavior can be observed obviously, which is compatible with the heat capacity results obtained by Hamdeh et al [18]. But they still have no proof for either the magnetization or Mo¨ssbauer results.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…For the ZFC curve with 10 Oe magnetic field applied, spin-glass behavior can be observed obviously, which is compatible with the heat capacity results obtained by Hamdeh et al [18]. But they still have no proof for either the magnetization or Mo¨ssbauer results.…”
Section: Resultssupporting
confidence: 82%
“…Spin-glass behavior was also predicted in nanosized ZnFe 2 O 4 particles by Oliver [15][16][17]. And what is more, according to the above reports of ferrimagnetism of ZnFe 2 O 4 nanoparticles, ball-milling process has to be included [4,12,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Various chemical methods such as co-precipitation [18], sol-gel [19], molten saltroute [20], ultrasonic radiation [21], tartrate precursor [22], electrodeposition [23], urea combustion [24], aerogel [25], mechanochemical [26], etc. have been developed to synthesize nanosized zinc ferrites.…”
Section: Introductionmentioning
confidence: 99%
“…The zinc ferrite in nanocrystalline form has been studied recently by many researchers [3e7]. Hamdeh et al found that inversion takes place in zinc ferrite at low temperature when synthesized in nanocrystalline size [3]. Ammar et al [4] observed ferrimagnetic behavior at low temperature and observed the size dependent canting in zinc nano-ferrite [4].…”
Section: Introductionmentioning
confidence: 99%